Hyperpolarization‐activated cation and T‐type calcium ion channel expression in porcine and human renal pacemaker tissues - Hurtado, Romulo (J Anat, 2016)
Renal pacemaker activity triggers peristaltic upper urinary tract contractions that propel waste from the kidney to the bladder, a process prone to congenital defects that are the leading cause of pediatric kidney failure. Recently, studies have discovered that hyperpolarization‐activated cation (HCN) and T‐type calcium (TTC) channel conductances underlie murine renal pacemaker activity, setting the origin and frequency and coordinating upper urinary tract peristalsis. Here, we determined whether this ion channel expression is conserved in the porcine and human urinary tracts, which share a distinct multicalyceal anatomy with multiple pacemaker sites. Double chromagenic immunohistochemistry revealed that HCN isoform 3 is highly expressed at the porcine minor calyces, the renal pacemaker tissues, whereas the kidney and urinary tract smooth muscle lacked this HCN expression. Immunofluorescent staining demonstrated that HCN (+) cells are integrated within the porcine calyx smooth muscle, and that they co‐express TTC channel isoform Cav3.2. In humans, the anatomic structure of the minor calyx pacemaker was assayed via hematoxylin and eosin analyses, and enabled the visualization of the calyx smooth muscle surrounding adjacent papillae. Strikingly, immunofluorescence revealed that HCN3(+)/Cav3.2(+) cells are also localized to the human minor calyx smooth muscle. Collectively, these data have elucidated a conserved molecular signature of HCN and TTC channel expression in porcine and human calyx pacemaker tissues. These findings provide evidence for the mechanisms that can drive renal pacemaker activity in the multi‐calyceal urinary tract, and potential causes of obstructive uropathies.